Titanium Alloys Advances in Properties Control - Sieniawski, Jan; Ziaja, Waldemar (IntechOpen, 2013)
The book contains six chapters and covers topics dealing with biomedical applications of titanium alloys, surface treatment, relationships between microstructure and mechanical and technological properties, and the effect of radiation on the structure of the titanium alloys.